Pluralism, transnationalism, and culture in Asian law : a book in honour of M.B. Hooker / edited by Gary F. Bell. - Bell, Gary F. (ISEAS Publishing, 2017)
"We owe much of our knowledge of legal diversity in Asia to the work of Barry Hooker, who appears early on to have appreciated its intrinsic interest and potentially global significance. His work in the field is, as the French say, incontournable; a nice combination of the unavoidable, the controlling and the greatly respected." - H.P. Glenn To honour this great scholar, this book gathers essays from admirers and friends who add their own contributions on legal pluralism, transnationalism and culture in Asia. The book opens with an account of M.B. Hooker colourful and prolific career. The authors then approach legal pluralism through legal theory, legal anthropology, comparative law, law and religion, constitutional law, even Islamic art, thus reflecting the broad approaches of Professor Hooker's scholarship. While most of the book focuses mainly on Southeast Asia, it also reaches out to all of Asia up to Israel, and even includes a chapter comparing Indonesia and Egypt.